1997
DOI: 10.2135/cropsci1997.0011183x003700060033x
|View full text |Cite
|
Sign up to set email alerts
|

Drought‐Resistance Mechanisms of Seven Warm‐Season Turfgrasses under Surface Soil Drying: II. Root Aspects

Abstract: Knowledge of drought‐resistance mechanisms in turfgrasses would improve management strategies and facilitate turfgrass breeding for drought resistance. The experiment investigated root morphological and physiological characteristics in response to surface soil drying and rewatering for bermudagrass [Cynodon dactylon (L.) Pers. ‘Common’], centipedegrass [Eremochloa ophiuroides (Munro) Hack ‘Tif‐Blair’], seashore paspalum (Paspalum vaginatum Swartz, four ecotypes), and zoysiagrass (Zoysia japonica Steudel × Z. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
126
1
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 0 publications
10
126
1
5
Order By: Relevance
“…AMES-10107 and CM-614 showed stability in total root length under drought stress when compared with non-stress regime. Huang et al (1997) found that, although total root length influences water and nutrient uptake, root growth maintenance during drought was more important for plant tolerance to drought.…”
Section: Discussionmentioning
confidence: 99%
“…AMES-10107 and CM-614 showed stability in total root length under drought stress when compared with non-stress regime. Huang et al (1997) found that, although total root length influences water and nutrient uptake, root growth maintenance during drought was more important for plant tolerance to drought.…”
Section: Discussionmentioning
confidence: 99%
“…In general, plant urease activities and root uptake of N and water can affect the magnitudes of NH 3 volatilization (Frankenberger and Tabatabai 1982), N leaching (Bowman et al 2002;Crush et al 2005), and denitrification (Virginia et al 1982). C 4 , warm-season turf species are known for low water requirements (Huang et al 1997;Youngner et al 1981). In semi-arid urban ecosystems, these species may be associated with reduced water and N inputs and smaller ecosystem N losses relative to C 3 , cool-season species because of higher productivity and high efficiencies in N and water use under warm temperatures (Long 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these discrepancies, the work was still carried out using clay soils because such soils were the primary type of soils in Singapore in which most lawns were constructed and grown from. In addition, it is noteworthy that apart from the soil and climatic environment, the ability for deep rooting is another important component of drought resistance in turfgrasses (Huang et al, 1997;Qian and Engelke, 1999;Zhang et al, 2013;Zhang and Unruh, 2015). Drier conditions tended to stimulate greater allocation towards root rather than shoot biomass (Table 5).…”
Section: -73mentioning
confidence: 99%